A survey of dog and cat anaesthesia in a sample of veterinary practices in New Zealand. Issue 2 (4th March 2018) - Sano, H; Barker, K; Odom, T; Lewis, K; Giordano, P; Walsh, V; Chambers, JP
Abstract : AIMS: To survey current anaesthesia practices for dogs and cats in small and mixed animal practices in New Zealand in order to improve anaesthesia education. METHODS: A questionnaire was sent to 440 small and mixed animal practices, including questions regarding the type of practice, preanaesthetic examination, anaesthetic drugs and management, anaesthetic machines, monitoring and topics of interest for continuing professional development. RESULTS: Responses were obtained from 113/440 (26%) practices, with 78 (69%) respondents from small and 35 (31%) from mixed animal practices. A preanaesthetic physical examination was carried out by >95% of respondents and premedication was usually given to dogs (112/113; 99%) and cats (95/113; 85%). Acepromazine was the preferred sedative for dogs and cats, with morphine or buprenorphine. Propofol and alfaxalone were the preferred induction agents, and isoflurane was preferred for maintenance in both dogs and cats. A venous catheter was usually placed for anaesthesia in dogs (59/113; 52%), but less so in cats (39/113; 35%). Perioperative fluid was administered at 10 mL/kg/hour by 62/110 (56%) respondents. Intubation was usually used for anaesthesia in dogs (111/112; 99%), and cats (87/112; 78%). Almost 40% of respondents usually administered supplementary oxygen if patients were not intubated. Local analgesia was used by 69/111 (88%) respondents sometimes or always if applicable. Morphine or buprenorphine, and meloxicam were common choices for post-operative analgesia after neuter surgery in dogs and cats. A semiclosed (non-rebreathing) system was used in animals weighing <10 kg, and a Mapleson E or F non-rebreathing circuit was used by 66/109 (61%) practices. Only 15/111 (14%) practices had a ventilator in their practice. A dedicated anaesthetist was usually used by 104/113 (92%) practices, and apnoea alarms, pulse oximeters, thermometers and oesophageal stethoscopes were the main monitoring devices available in practices. Loco-regional block, pain management, and anaesthetic drugs were the main topics of interest for continuing education. CONCLUSIONS AND CLINICAL RELEVANCE: Responses by the veterinarians taking part in this survey indicated that they had a reasonably good standard of anaesthetic practice. A physical examination was carried out preanaesthesia, and premedication including analgesia was routinely administered to most patients. A dedicated anaesthetist usually monitored patients and most respondents reported they had access to basic anaesthetic monitoring equipment. Areas where changes could lead to improved anaesthetic practice were increased use of I/V catheterisation, endotracheal intubation, and supplementary oxygen, and reduced I/V fluid rates.